Cerium‐Doped Perovskite Nanocrystals for Extremely High‐Performance Deep‐Ultraviolet Photoelectric Detection. Issue 22 (23rd September 2021) - Li, Dongyu; Xu, Wen; Zhou, Donglei; Ji, Yanan; Ding, Nan; Chen, Xu; Zhu, Jinyang; Sun, Rui; Lu, Siyu; Ma, Chonggeng; Jia, Zhixu; Qin, Guanshi; et al.
Abstract: In this study, a novel deep‐ultraviolet photodetector (DUVPD) based on the hybrids of solution‐processed CsPbX3 (X = Cl, Br):Ce 3+ perovskite nanocrystals (PNCs) and plasmonic Al film is presented. The optical absorption strength of the CsPbX3 :Ce 3+ PNCs is improved by one order of magnitude in the solar‐blind DUV range (200–280 nm) compared with the undoped. First‐principles calculations and Dorenbos's 4f and 5d host referred binding energy (HRBE) models prove that such an improvement results from the 4f–5d transition of Ce 3+ . The presence of Al film further improves the optical absorption strength in this DUV range due to the plasmonic effect and the metal−perovskite junction between Al film and perovskite. Finally, the DUVPDs based on CsPbCl3 :Ce 3+ /Al hybrids demonstrate extremely high detectivity of 4 × 10 13 Jones. This work is the first approach to build up high‐performance DUVPDs based on the doped PNCs. Abstract : A novel deep ultraviolet photodetector based on the hybrids of solution‐processed CsPbX3 (X = Cl, Br):Ce 3+ perovskite nanocrystals and plasmonic Al film is presented and extremely high detectivity of 4 × 10 13 Jones is demonstrated, attributed to the significantly enhanced optical absorption strength in this deep‐ultraviolet (DUV) range by Ce 3+ doping and plasmonic Al film.